The effect of ultrafast heating rate on the elemental distribution between phases in a low carbon steel. Issue 1 (31st December 2022) - Valdes-Tabernero, M. A.; Monclus, M. A.; Sabirov, I.; Molina-Aldareguia, J. M.; Petrov, R. H.; Wang, J.; Timokhina, I.
Abstract: This work focuses on the effect of heating rate, i.e. conventional heating (CH) and ultrafast heating (UFH) rates on the elemental distribution between phases in a low carbon steel. Microstructural characterization was carried out using an Electron Backscatter Diffraction (EBSD) and Atom Probe Tomography (APT) technique. Nanohardness of individual microconstituents was measured. It is shown that the applied heat treatments result in the formation of multiphase microstructures consisting of a ferritic matrix with embedded martensite and retained austenite. The ferritic matrix of the CH material was fully recrystallized, whereas both recrystallized (coarser) and non-recrystallized (finer) ferritic grains were present in the matrix of the UFH material. APT analysis indirectly confirmed that recrystallized grains after both heat treatments have a lower carbon content, when the non-recrystallized grains after UFH have a higher carbon content. It correlates with the nanohardness results, i.e. non-recrystallized grains show higher hardness, while recrystallized grains have a lower hardness. The segregations of C and Mn atoms at the martensite/ferrite interface were observed after both treatments. It is hypothesized that the segregations are formed under negligible partitioning local equilibrium condition during CH, whereas the solute drag effect results in the formation of interface segregation during UFH.